Enzyme-Doped Graphene Nanosheets for Enhanced Glucose Biosensing - Alwarappan, Subbiah; Liu, Chang; Kumar, Ashok; Li, Chen-Zhong (Journal of physical chemistry. C, 2010)
In this work, we report the enhanced performance of polypyrrole−graphene−glucose oxidase based enzymatic biosensors employed for in vitro electrochemical glucose detection. Initially, graphene nanosheets were chemically synthesized and surface morphologies were characterized by several physical methods. Following this, graphene nanosheets were covalently conjugated to an enzyme model glucose oxidase (GOD). The presence of various reactive functionalities such as ketonic, quinonic, and carboxylic functional groups on the edge plane of graphene easily binds with the free amine terminals of the glucose oxidase to result in a strong covalent amide linkage. Further, this covalent conjugation of the enzyme to graphene was confirmed by FT-IR measurements. Following this, the surface of a glassy carbon electrode was modified by polypyrrole. Later, the conjugated graphene−GOD were then immobilized onto the glassy carbon electrode surface already modified with polypyrrole (Ppy) and the entire assembly was employed for glucose detection. Results indicated that the electrodes immobilized with graphene conjugated to GOD exhibited a better sensitivity and response time than the electrodes immobilized with graphene alone. The observed results indicate that the 2D graphene holds great promise to be conjugated with a variety of enzymes. Besides conjugation, the entrapment of graphene−GOD within the porous structure of Ppy will hold the enzyme in a favorable position, thereby retaining the original structure and functionality of the enzymes that account for high-performance biosensing.